THE ECONOMIC DOCTRINES WITH THEIR PRINCIPLES AND HIS PRECEPTS - Bortesi Longhi, Luis (2014)
The economic doctrines are the ethical and technical foundations that theoretically are more convenient, advisable and fair to access development. Therefore, the philosophical argument aims to demonstrate what should be the priorities that could drive and what should be the economic policy strategies to secure progress. So that the structure of an economic doctrine comprises three strands:1° Budgets or starting hypothesis where basic a priori assumptions are set out. This aspect naturally depends, of the intellectual formation of the author responsible for doctrine.2° Observations or findings of fact of the development of the model and its applications effects.3° Standards; that is to say, the formulation of qua-litative and philosophical precepts underlying the praxis and institutionalized execution of the economic system.